Industrial recycling of end-of-life vehicle windshield glass by mechanical beneficiation and complete recovery of polyvinyl butyral. (1st February 2022) - Swain, Basudev; Park, Jae Ryang; Lee, Chan Gi
Abstract: The environmental concern of end-of-life vehicles and stringent environmental regulation like the resource conservation and recovery act of the USA, and registration, evaluation, authorization, and restriction of chemicals act of EU and Korea mandates the recycling of the ELV. The EU-Directive 2000/53/EC on end-of-life vehicles was enacted in 2000, imposed a target to recycle for reuse and recovery at 85 and 80% by 2006; and then 95 and 85%, by 2015, respectively. Hence, recycling process development for each component like metal, plastic, glass, and rubber from end-of-life vehicles is essential. In the current investigation, an industrial-scale recycling process for end-of-life vehicle windshield glass has been developed for the recovery of polyvinyl butyral and glass components by mechanical beneficiation technique. In the developed process the industrial-scale recycling of end-of-life vehicle windshield glass and valorization of polyvinyl butyral broadly integrates two important processes i.e., (i) size reduction, and (ii) separation of constituent materials, and five different stages. The size reduction process involves (i) shredding and (ii) crushing followed by shredding. The separation process sequentially follows (i) polyvinyl butyral sheet and glass powder separation, (ii) crushing and gravity separation, and (iii) polyvinyl butyral recovery by rubbing and pressure washing process. The process flowsheet is developed for continuous operation with a capacity of up to 8–10 tons per day. An average of 98.86% of polyvinyl butyral recovery and 99.26% of glass recovery efficiency was achieved, which can be considered quantitative enough for industrial-scale recovery. Graphical abstract: Image 1 Highlights: An industrial recycling process for automotive windshield glass has been developed. The valorization process can separate PVB/glass from windshield glass. Both separated PVB and glass can be used for remanufacturing. The process is a simple and versatile mechanical separation process. Average 98.86% PVB and 99.26% glass recovery efficiency were achieved.